Ischemia/Reperfusion Injury in the Aged Liver: The Importance of the Sinusoidal Endothelium in Developing Therapeutic Strategies for the Elderly. (14th January 2019) - Hide, Diana; Warren, Alessandra; Fernández-Iglesias, Anabel; Maeso-Díaz, Raquel; Peralta, Carmen; Le Couteur, David G; Bosch, Jaime; Cogger, Victoria C; Gracia-Sancho, Jordi
Abstract: The liver endothelium plays a key role in the progression and resolution of liver diseases in young and adult individuals. However, its role in older people remains unknown. We have herein evaluated the importance of the sinusoidal endothelium in the pathophysiology of acute liver injury, and investigated the applicability of simvastatin, in aged animals. Eighteen-months-old male Wistar rats underwent 60 minutes of partial warm ischemia followed by 2 hours of reperfusion (WIR). A group of aged rats received simvastatin for 3 days before WIR. Endothelial phenotype, parenchymal injury, oxidative and nitrosative stress, and fenestrae dynamics were analyzed. The effects of WIR and simvastatin were investigated in primary LSEC from aged animals. The results of this study demonstrated that WIR significantly damages the liver endothelium and its effects are markedly worse in old animals. WIR-aged livers exhibited reduced vasodilation and sinusoidal capillarization, associated with liver damage and cellular stress. Simvastatin prevented the detrimental effects of WIR in aged livers. In conclusion, the liver sinusoidal endothelium of old animals is highly vulnerable to acute insult, thus targeted protection is especially relevant in preventing liver damage. Simvastatin represents a useful therapeutic strategy in aging.